PERANCANGAN DAN PEMBUATAN SENSOR SUHU - ., Sutrisno (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Thermometer is a device which is generally used to measure and is used to determine the level of temperature that is around. With the increasingly rapid technological advances in recent years, particularly in electronics so that the man with the intellect and the mind is trying to develop a thermometer that can be used as needed. One result of the development of the electronic thermometer. This thermometer will display the temperature measured into digital form so that the thermometer is increasingly used in electronic equipment. In this study will be designed to measure the temperature of the CPU, this is done in consideration of the importance of a temperature control on the CPU. Purpose of the design and manufacture of these tools is to make hardware that can check the CPU temperature. This is done in consideration of the importance of a temperature control on the CPU so the CPU can anticipate the damage caused by warming temperatures. So that the temperature changes inside the casing that is activated by the use of too long. Keywords: Temperature Sensor, CPU